2008
DOI: 10.1108/00070700810893313
|View full text |Cite
|
Sign up to set email alerts
|

Food safety practices in milk collection centers in Turkey: a case study

Abstract: Purpose -The aim of this study was to reveal the role and importance of the milk collection centers in İzmir in assuring food safety in the Turkish dairy sector. Design/methodology/approach -A five-point Likert scale was applied to collect data on the food safety practices and the problems confronted in MCCs. The difference between the groups in the managers' and MCCs' specifications and the food safety applications in the MCCs were determined by one-way ANOVA for continuous variables. For the continuous varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…European Union (EU) milk quality levels are only reached by a limited number of large scale dairy farms. This was documented in a recent study on the role and importance of the milk collection centers in Izmir 11 . It was found that quality control analysis of raw milk cannot be carried out because of the lack of qualified specialists and equipment inadequacies.…”
Section: Introductionmentioning
confidence: 76%
“…European Union (EU) milk quality levels are only reached by a limited number of large scale dairy farms. This was documented in a recent study on the role and importance of the milk collection centers in Izmir 11 . It was found that quality control analysis of raw milk cannot be carried out because of the lack of qualified specialists and equipment inadequacies.…”
Section: Introductionmentioning
confidence: 76%
“…Three-milliliter aliquots of milk sample were mixed with 3 mL of 70% (vol/vol) alcohol in a dish and observed for 10 to 20 s. If flocculent precipitates appeared in the milk, the milk was regarded as alcohol positive, indicating spoilage of the pasteurized milk. Otherwise, the sample was determined to be alcohol-negative milk (Demirbas et al, 2008).…”
Section: Alcohol Test Of Pasteurized Milkmentioning
confidence: 99%
“…Adding 70% alcohol to high-acid milk results in milk protein precipitation. This phenomenon is called an alcohol positive test, which is an important sign of milk deterioration (Demirbas et al, 2008). The effect of different GBP concentrations on the alcohol test of pasteurized milk within 21 d of storage is shown in Table 2.…”
Section: Effect Of Gbp On Alcohol Test Of Pasteurized Milkmentioning
confidence: 99%
“…However, little research exists on food safety practices in dairy businesses (Demirbas & Karagozlu, 2007, 2008Young et al, 2010) and milk collection centers (Armagan, Koc, & Ozden, 2009;Demirbas, Golge, Tosun, & Cukur, 2008). Moreover, no study exists that includes all dairy businesses located in one city and little has been written about the effectiveness of food safety training in Turkish dairy businesses.…”
Section: Introductionmentioning
confidence: 96%